The influence of tocotrienol on the development of preimplantation embryos, implantation sites and pregnancy outcomes in corticosterone-treated mice / Nuraliza Abdul Satar, Mohd Hamim Rajikin and Nor Ashikin Mohamed Noor Khan - Abdul Satar, Nuraliza; Rajikin, Mohd Hamim; Mohamed Noor Khan, Nor Ashikin (Research Management Institute (RMI), 2011)
Stress is an attribute of modern life style. Stress is a daily problem encountered by men and women where it affects reproductive system and could influence fertility (Senders & Bruce, 1997; Vilar, 1993). Fertility issues on couples have been widely discussed around the world. It has been estimated that in 2002, about 35 to 70 million couples worldwide are infertile and have turned to Assisted Reproductive Technology (ART) to overcome their infertility (Schultz & Williams, 2002). Stress results in enhanced release of glucocorticoid due to activation of sympathoadrenals and hypothalamic-pituitary-adrenal axis. Increased glucocorticoid levels, i.e. cortisol in human and corticosterone (CORT) in rodents are indication of stress (Joels et al., 2007). Several stages of normal reproductive process could be disturbed by stress (Euker & Riegle, 1973). Adrenocortical activation during the preimplantation phase may inhibit fertility in women (Rowel, 1970). “Stress” was defined as teratogenic and CORT is the most probable adrenal steroid hormone involved in mouse under stress condition (Hackman & Brown, 1972). In human, early pregnancy loss is attributed by maternal stress as indicated by increased cortisol levels (Nepomnaschy et al., 2006). Exogenous CORT administration during second term of pregnancy in rodents resulted in an increased frequency of totally resorbed litters, where the effect seen is directly proportional to the dose of CORT administration (Hackman & Brown, 1972). However, the mechanisms that affect the reproductive system in that study remain unclear…